PENILAIAN HASIL BELAJAR SISWA PADA KURIKULUM MERDEKA DI SEKOLAH DASAR - Saputra, Hardian; Saputra, Ritho Apriyandi; Julianto, Jefry; Ramadhani, Aulya (Information Technology Education Department, 2025)
The purpose of this study is to examine the extent of the application of learning assessments that align with the Independent Curriculum at Sekolah Dasar Negeri 001/V Kuala Tungkal. This research is qualitative and descriptive. It involves the principal and two classroom teachers from Sekolah Dasar Negeri 001/V as the data sources. Data collection was conducted through observation, interviews, processing data from research materials, reading and noting relevant information, as well as data from various literature sources. Using a descriptive qualitative research methodology, data was collected through literature review/library studies. The research results concluded that the curriculum learning assessment at Sekolah Dasar Negeri 001/V covers three assessment domains: affective, cognitive, and psychomotor, whereas the assessment process is carried out through five main stages consisting of reviewing the syllabus, making assessment grids, conducting assessment activities, analyzing assessment results, and compiling assessment reports. Based on these findings, it is recommended that learning assessment continues to be carried out by paying attention to the established assessment standards.